Pengarlth penggantian daging sapi dengan dagingkerbau, ayam dan kelinci pada komposisi dan kualitas fisik baso - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
The experiment was done to study the effect of beef substitution with buffalo, chicken and rabbit meat on chemical and physical property of haso. The Longissimus dorsi muscle of beef and buffalo, rabbit and chicken meat, egg and seasoning were used in this study. The principles of baso making was substituted by (buffalo, chicken and rabbit) meat and the level of substitution namely: 0, 25, 50, 75 and 100%, respectively. The chemical composition was water, protein, fat and ash content, and the physical properties were tenderness, cooking loss and water holding capacity (WHC). The organoleptical test was toughness, texture, color and taste by panelist test. Data were analysed by using a 3 x 5 factorial of variance analyses (Steel and Torrie, 1980). The results indicated that there were significant effects (P... Kata kunci: Kualitas fisik, Baso sapi, Penggantian daging, kerbau, ayam, kelinci